2007
DOI: 10.1007/s12032-007-9031-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum MMP-2 and MMP-7 in patients with ovarian cancer

Abstract: Matrix metalloproteinases (MMPs) are frequently expressed in malignant tumors and play an important role in tumor invasion and metastasis. The aim of this study was to evaluate role of serum MMP-2 and MMP-7 levels in patients with ovarian cancer. Serum levels of MMP-2 and MMP-7 were measured in 28 patients with ovarian carcinoma, 2 with borderline ovarian tumors, 10 with non-malignant gynecological disease and 30 healthy women by Enzyme-Linked Immunosorbent Assay (ELISA). Serum MMP-7 level was significantly (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
2
27
3
Order By: Relevance
“…21,32 We found that serum levels of MMP7 were increased in the allograft recipients and that this increase was genotype-and haplotype-dependent. These data indicate that MMP7 genotype has an effect on protein levels but only under conditions of cellular stress, such as after lung transplantation, and not during steady-state conditions, such as in healthy individuals.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…21,32 We found that serum levels of MMP7 were increased in the allograft recipients and that this increase was genotype-and haplotype-dependent. These data indicate that MMP7 genotype has an effect on protein levels but only under conditions of cellular stress, such as after lung transplantation, and not during steady-state conditions, such as in healthy individuals.…”
Section: Discussionmentioning
confidence: 80%
“…[12][13][14] MMP-7 thus far has not been studied in the context of BOS, although its function has been established in fibrotic lung diseases such as idiopathic pulmonary fibrosis and, in particular, the development of various cancers. [15][16][17][18][19][20][21] MMP-7 has a broad substrate specificity, being able to degrade elastin, proteoglycans, type IV collagen, and other components found in the lung matrix. 9,22 It is a protein constitutively produced by the epithelium of several noninjured, non-inflamed tissues, such as lung, liver, and breast.…”
mentioning
confidence: 99%
“…However, they did note that activated MMP-2 levels were related to disease invasiveness, metastasis and progression. Increased serum MMP-7 levels have also been found in patients with malignant ovarian tumors, using ELISA [82], while high-levels of MMP-14 expression have been recently reported to contribute to both the proliferative capacity and the enhanced parenchymal metastasis of ovarian clear cell carcinoma [83]. Studies investigating the role of MMPs in polycystic ovary syndrome (PCOS), have noted that women with PCOS have significantly higher serum concentrations of MMP-2, -9 and TIMP-1 but not TIMP-2 [84,85].…”
Section: Role Of Mmps In Ovarian Cancermentioning
confidence: 99%
“…Rauvala et al [129] concluded that the sequential measurement of serum MMP-2, MMP-9 and TIMP-2 during chemotherapy of optimally operated patients might be useful for treatment response evaluation. More importantly, Acar et al [82] concluded that serum MMP-7 could be a useful marker of disease activity in malignant ovarian tumors, since its preoperative levels were significantly (p < 0.05) lower compared with postoperative ones (10.24 ± 1.35 ng/ml and 7.68 ± 1.17 ng/ml respectively).…”
Section: Mmps As Diagnostic Tools and Markers Of Disease Progressionmentioning
confidence: 99%
“…In 2016, Niedworok and his colleagues' findings also showed elevated serum levels in metastatic compared to non-metastatic RCC cases (19). Thus, MMP-7, in addition to carbonic anhydrase IX, VEGF, IL-6 and CRP, may serve as a promising serum marker for the detection of metastasis and prediction of poor survival for RCC, similarly to other cancers including gastric (22), colorectal (23,24) and ovarian cancer (25). There are several limitations in this study.…”
Section: Discussionmentioning
confidence: 75%